2012
DOI: 10.1177/0300985812456215
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Features of Oxalate Nephrosis in a Population of Koalas (Phascolarctos cinereus) in South Australia

Abstract: The wild and captive koala population of the Mt Lofty Ranges in South Australia has a high level of renal dysfunction in which crystals consistent with calcium oxalate have been observed in the kidneys. This study aimed to describe the pathological features of the renal disease in this population, confirm the composition of renal crystals as calcium oxalate, and determine whether any age or sex predispositions exist for this disease. A total of 51 koalas (28 wild rescues, 23 captive) were examined at necropsy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
56
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 17 publications
5
56
2
Order By: Relevance
“…Postmortem examination revealed bilateral, moderate, chronic-active neutrophilic and lymphocytic keratitis with corneal neovascularisation consistent with ocular chlamydiosis (Wan et al, 2011). There was mild prostatic cystic glandular dilation with mild hyperplasia and fibrosis; mild chronic nonsuppurative and rarely neutrophilic urethritis; and bilateral renal lesions characterized by segmental tubular ectasia, tubular epithelial degeneration, mild intratubular inflammation, ghosts of crystal rosettes formed by finely radiating spicules, and mild interstitial fibrosis consistent with oxalate nephrosis (Speight et al, 2012). Conjunctivae were not examined histologically.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Postmortem examination revealed bilateral, moderate, chronic-active neutrophilic and lymphocytic keratitis with corneal neovascularisation consistent with ocular chlamydiosis (Wan et al, 2011). There was mild prostatic cystic glandular dilation with mild hyperplasia and fibrosis; mild chronic nonsuppurative and rarely neutrophilic urethritis; and bilateral renal lesions characterized by segmental tubular ectasia, tubular epithelial degeneration, mild intratubular inflammation, ghosts of crystal rosettes formed by finely radiating spicules, and mild interstitial fibrosis consistent with oxalate nephrosis (Speight et al, 2012). Conjunctivae were not examined histologically.…”
mentioning
confidence: 99%
“…The Mount Lofty population is subject to fragmentation of habitat, motor vehicle injury, predation by dogs, urbanization, limited genetic diversity, and a high incidence of renal disease (Speight et al, 2012). The koala retrovirus has been reported in the Kangaroo Island population in South Australia (Simmons et al, 2012).…”
mentioning
confidence: 99%
“…Only one possible inherited disease of marsupials has been reported, a suspected lysosomal storage disease in two individual kangaroos. 20 Dietary oxalate levels were not considered high enough to cause the syndrome in this case, 23 nor in a case of multiple koalas in a captive colony in Western Australia. 22 A study of a group of koalas in South Australia found 28/51 captive and rescued wild koalas exhibited gross and/or histological evidence of renal oxalate crystal deposition.…”
Section: Discussionmentioning
confidence: 81%
“…17 Reports of RO in other marsupials include cases in koalas, [18][19][20] wombats 21 and single cases in a scaly-tailed possum and a swamp wallaby. 20 A defect in oxalate metabolism similar to that seen in Gilbert's potoroo might be considered in cases of RO in other marsupials. 20 Dietary oxalate levels were not considered high enough to cause the syndrome in this case, 23 nor in a case of multiple koalas in a captive colony in Western Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Ethylene glycol poisoning was described in a raccoon Procyon lotor, a polar bear Ursus maritimus, and a captive-bred released California condor Gymnogyps californianus (Amstrup et al 1989, Murnane et al 1995, Foley & McBurney 2002. Oxalate deposition has been reported in koala Phascolarcotos cinereus, white-tailed deer Odo co ileus virginianus, green turtle Chelonia mydas, desert tortoise Gopherus agassizii, baboon Papio ursinus, and Ja pa nese macaque Macaca fuscata (Wyand et al 1971, McConnell et al 1974, Yanai et al 1995, Stacy et al 2008, Jacobson et al 2009, Speight et al 2013. In these cases, most animals were asymp tomatic, and these occurrences were presumed to result from the ingestion of oxalate-rich plants.…”
Section: Discussionmentioning
confidence: 99%